KITAB KUNING AND TRAINING OF ‘ULAMÂ’: The Experience of Madrasah Al Qismul Ali Jalan Ismailiyah Medan - Asari, Hasan; Abidin, Zainal (MIQOT: Jurnal Ilmu-ilmu Keislaman, 2020)
Abstract: This article is a result of a history research relying on informants and documents for the larger part of its data. The Madrasah Al Qismul Ali Jalan Ismailiyah Medan was established by Al Jam’iyatul Washliyah in 1953, to cater for the education of young ‘ulamâ’ applying a curriculum almost solely based on Islamic classical books (known popularly as kitab kuning). This madrasa was very successful in fulfilling its mission and was celebrated as an‘ulamâ’-producing institution until mid-1980s. Madrasah Al Qismul Ali strives to combine its old winning curriculum with the new state-sponsored one. After some decades, it is clear that this strategy is not working to expectation. The madrasa fails to deliver graduates of the same quality as it did. Apparently what is left of classical book in the curriculum is not sufficient to prepare younger generation of ‘ulamâ’.Keywords: Qismul Ali, kitab kuning, ‘ulamâ’ training, madrasah